Clinical oncologic applications of PET/MRI: a new horizon - Partovi, Sasan (e-Century Publishing Corporation, 2014)
Positron emission tomography/magnetic resonance imaging (PET/MRI) leverages the high soft-tissue contrast and the functional sequences of MR with the molecular information of PET in one single, hybrid imaging technology. This technology, which was recently introduced into the clinical arena in a few medical centers worldwide, provides information about tumor biology and microenvironment. Studies on indirect PET/MRI (use of positron emission tomography/computed tomography (PET/CT) images software fused with MRI images) have already generated interesting preliminary data to pave the ground for potential applications of PET/MRI. These initial data convey that PET/MRI is promising in neuro-oncology and head & neck cancer applications as well as neoplasms in the abdomen and pelvis. The pediatric and young adult oncology population requiring frequent follow-up studies as well as pregnant woman might benefit from PET/MRI due to its lower ionizing radiation dose. The indication and planning of therapeutic interventions and specifically radiation therapy in individual patients could be and to a certain extent are already facilitated by performing PET/MRI. The objective of this article is to discuss potential clinical oncology indications of PET/MRI.